Caracterização e avaliação de dois sistemas agroflorestais no Sudoeste Paulista - Garcia, Vinícius José de Oliveira (Universidade Federal de São Carlos, 2022)
The agroforestry systems have been presenting a great interest of research around Brazil and the world as an option of agricultural form contrary to monoculture and which prioritize the conservation of biodiversity and soil, besides presenting productive power and social and ecological development. However, there are some hurdles that hinder the broad adhering to this model, especially in the different contexts of family farming, mainly due to the absence of public funding policies and specialised technical assistance. Consequently, the management of these systems becomes a complex task for farmers , since it is a multidimensional system that correlates the social, economic and environmental spheres simultaneously. The present work uses participatory characterization altogether with indicators with two family farmers who own agroforestry systems implemented in the years 2018 and 2019 as part of a university extension project linked to the Lagoa do Sino Campus of UFSCar, in the counties of Itabera–SP and Buri–SP. An assessment of multidimensionality was carried out in order to investigate the internal and external benefits and barriers to the system, based on literature and farmers reports, systematizing knowledge for a better management and appropriation of this sustainable agriculture system.
Characterization and evaluation of two agroforestry systems in the Southwest of São Paulo state
Keywords: Agricultura familiar; Agroecossistemas; Indicadores; Sistemas agroflorestais; Agroecosystem; Agroforestry systems; Family farming; Indicators; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL